A touch switch with 3D effect
By using a capacitive touch technology of transparent insulating layer and conductive oil in the film switch, the problem of insufficient contact between the upper contacts of the control circuit and the lower plate is solved, and a longer service life and higher installation accuracy are achieved.
Patent Information
- Application Number
- CN202111122755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2041-09-24
AI Technical Summary
During continuous pressing of the film switch, the upper contacts of the control circuit and the lower plate of the control circuit are insufficiently in contact with the insensitive control circuit, which affects the service life.
The transparent insulating layer and conductive oil are used to achieve capacitive touch effect through conductive oil, the touch circuit is controlled by changing the capacitor, and hot melt adhesive, heating agent and initiator are used in the adhesive layer to achieve high accuracy of pasting and installation.
It effectively avoids insufficient contact with the contacts and the electrode plate after multiple contacts, improves the service life of the touch switch, and improves the installation accuracy and aesthetics through high-precision pasting technology.
Smart Images

Figure CN113852366B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of thin film electronic devices, and more specifically, to a touch switch with a 3D effect. Background Art
[0002] Membrane switch is an operating system that integrates key functions, indicating elements, and instrument panels. It is made of several layers of films made of different materials, and the thickness is about 1.2-2.5mm. It has the dual functions of panel and switch. Since the membrane switch has a short action stroke of only about 0.25-0.5mm, the switch pressing force is 0.5-1N, which is relatively sensitive. The switch function is completed with a light touch of the hand, so it is also called a touch switch. The touch switch has good sealing, moisture resistance, and long service life. It is widely used in electronic measuring instruments, automotive industry, household appliances and other fields.
[0003] At present, commonly used touch switches are mainly processed and prepared by panel layer, surface adhesive layer, upper control circuit layer, lower control circuit layer, interlayer layer and back adhesive layer. The surface of the panel layer is usually printed with patterns, which serves as a logo and button; the surface adhesive layer is mainly used to seal the panel layer and the control circuit layer; the upper control circuit layer and the lower control circuit layer play the role of conducting signals; the interlayer layer plays the role of sealing and connecting the upper control circuit layer and the lower control circuit layer, and the back adhesive layer is mainly used to stick the touch switch to the carrier.
[0004] When the membrane switch needs to be operated, the membrane switch is pressed, and the contacts on the upper layer of the control circuit are deformed downward and come into contact with the plates on the lower layer of the control circuit to be connected; after releasing the contact, the contacts on the upper layer of the control circuit bounce back, the circuit is disconnected, and the loop triggers a signal to control the operation of the corresponding equipment.
[0005] With respect to the above-mentioned related technologies, the inventors believe that when the above-mentioned membrane switch is continuously pressed and used, there may be a problem of insufficient contact between the upper contacts of the control circuit and the lower plates of the control circuit, which may cause the membrane switch to become insensitive to control, thereby affecting the normal service life of the membrane switch. Summary of the invention
[0006] In order to improve the problem that the upper contact of the control circuit and the lower plate of the control circuit may not be in sufficient contact with each other in a membrane switch, thereby affecting the service life of the membrane switch, the present application provides a touch switch with a 3D effect.
[0007] The touch switch with 3D effect provided in this application adopts the following technical solution:
[0008] A touch switch with a 3D effect comprises a pattern layer, a substrate and a touch switch circuit which are arranged in sequence, wherein the touch switch circuit is provided with conductive oil, carbon paste, silver paste circuit and a transparent insulating layer in sequence from the pattern layer to the substrate, and an adhesive layer is provided at the pattern layer or the transparent insulating layer.
[0009] By adopting the above technical solution, the transparent insulating layer and the conductive oil are used. Compared with the original contact and connection method between the upper contact of the control circuit and the lower plate of the control circuit, the insufficient contact between the contact and the plate after multiple contacts is avoided as much as possible. The capacitive touch effect is achieved by conductive oil, and the change of capacitance is used to control the touch circuit, which can improve the service life of the touch switch to a certain extent. The setting of the adhesive layer allows the staff to adjust the position of the adhesive layer according to the final pasting requirements and fit the entire touch switch to the upper or lower surface of the target component.
[0010] Preferably, the adhesive layer is composed of hot melt adhesive, the adhesive layer is provided with a plurality of microgrooves at intervals, and connecting channels respectively connected to the microgrooves, the connecting channels are connected to the outside, and an initiator and a heat-generating agent are arranged in the microgrooves.
[0011] By adopting the above technical solution, the characteristics of hot melt adhesive are utilized. It is solid and non-sticky at room temperature. After heating to a certain temperature, it softens and becomes sticky. Therefore, after the touch switch is produced and processed, there is no need to attach release paper to the adhesive layer, thereby achieving the purpose of environmental protection and saving processing steps.
[0012] When the touch switch needs to be installed on the surface of the device, the adhesive layer is made of ordinary glue and release paper. The user needs to peel off the release paper from the ordinary glue surface, align the touch switch with the installation position and press it to install the touch switch. However, the method of peeling off the release paper to install the touch switch on the surface of the device may easily cause the touch switch to deviate from the installation position, thereby affecting the installation accuracy and aesthetics of the touch switch.
[0013] By using a combination of hot melt adhesive, heating agent, initiator and microgrooves, the user only needs to align the touch switch with the installation position, and then use the initiator to induce the heating agent to produce a heating effect, so that the temperature of the hot melt adhesive gradually rises, and the hot melt adhesive further softens and becomes sticky, so that the touch switch is initially adhered to the surface of the device, thereby achieving initial fixation of the touch switch, and then the center part of the touch switch is heated and heated by a heating source, so that the hot melt adhesive in the center part of the touch switch softens and becomes sticky; after removing the heating source, the temperature of the hot melt adhesive drops and solidifies, thereby achieving the installation of the touch switch on the surface of the device, and to a certain extent improving the installation accuracy of the touch switch.
[0014] Preferably, a coating film is further provided in the adhesive layer, the coating film is placed in the microgroove, the initiator is placed in the coating film, and the heat-generating agent is located outside the coating film.
[0015] By adopting the above technical solution, the setting of the coating film can, on the one hand, protect the initiator and reduce the amount of initiator failure to a certain extent during the storage of the touch switch; on the other hand, it can isolate the initiator and the heating agent and reduce the probability of the two reacting to generate heat.
[0016] Preferably, the coating film is prepared into a sealed inner bubble film and an outer bubble film, the inner bubble film is placed in the microgroove and filled with nitrogen, the initiator is located in the inner bubble film, the outer bubble film is located outside the adhesive layer and filled with oxygen, and the pressure inside the outer bubble film and the inner bubble film is equal.
[0017] A connecting bridge is provided between the inner bubble membrane and the outer bubble membrane, a fixing ring is provided in the connecting bridge, the outer peripheral wall of the fixing ring is connected to the inner wall of the connecting bridge, a fixing tube is connected to the inner peripheral wall of the fixing ring, a piston is slidably connected in the fixing tube, through holes are provided on the side walls at both ends of the fixing tube, and the piston is located between the two through holes.
[0018] By adopting the above technical scheme, the inner bubble membrane and nitrogen are used in combination to make the initiator in a relatively stable storage environment, thereby reducing the amount of initiator failure during storage. At the same time, through the outer bubble membrane and oxygen, as well as the cooperation between the piston in the connecting bridge and the through hole on the fixed tube, the purpose of transporting oxygen into the inner bubble membrane and reacting with the initiator is achieved.
[0019] Preferably, the initiator is composed of Al powder and activated carbon in a mass ratio of (6-8):(5-7).
[0020] By adopting the above technical solution, the porous characteristics of the activated carbon surface are used as a carrier of Al powder. Compared with the method of Al powder agglomeration, the contact area between Al powder and oxygen in the air is increased, thereby increasing the degree of Al powder oxidation reaction to provide sufficient heat.
[0021] Since aluminum easily reacts with oxygen in the air and forms a dense oxide film on the surface, Al2O3 is prepared into Al2O3 powder by mechanical crushing, and then the Al2O3 powder is subjected to a reduction reaction to obtain sponge-like Al powder, so that the surface of the Al powder is rough with certain sponge-like gaps, thereby increasing the specific surface area and roughness of the Al powder; at the same time, activated carbon is used as a carrier of Al powder, which further increases the contact area between Al powder and oxygen compared to the Al powder agglomeration method, greatly increases the degree of reaction between Al powder and oxygen, and thus generates a large amount of heat.
[0022] Preferably, the exothermic agent is composed of sodium bicarbonate and calcium oxide in a mass ratio of (6-8): (2-3).
[0023] Al powder comes into contact with oxygen in the air to undergo an oxidation reaction and release heat, causing the temperature around the Al powder to rise. The sodium bicarbonate solid on the outside of the Al powder undergoes a decomposition reaction due to the heat, generating a small amount of water, sodium carbonate and carbon dioxide. The calcium oxide further reacts with the generated water, further releasing a large amount of heat, heating the hot melt adhesive, thereby softening the hot melt adhesive and making the hot melt adhesive sticky. Sodium bicarbonate plays a certain role in absorbing moisture during the storage process, preventing calcium oxide from gradually failing to a certain extent, and playing an auxiliary role; at the same time, in the process of adhering the touch switch, the sodium bicarbonate solid can undergo a decomposition reaction under the condition of rising temperature, generating water, carbon dioxide and sodium carbonate. Sodium bicarbonate plays the role of providing moisture for calcium oxide, causing calcium oxide to react with water to release a large amount of heat, thereby softening the hot melt adhesive at the edge of the touch switch, thereby realizing the initial positioning and installation function of the touch switch.
[0024] Preferably, the hot melt adhesive is made of the following raw materials in parts by weight:
[0025]
[0026] Preferably, the mass ratio of the dimethylolpropionic acid to sodium ethylenediaminoethanesulfonate is 1:1, and the mass ratio of the isophorone diisocyanate to hexamethylene diisocyanate is 2:1.
[0027] By adopting the above technical solution, polyurethane polymers are usually composed of soft segments and hard segments. The hard segment mainly affects the mechanical properties of the material, such as hardness and tensile strength; the soft segment mainly affects the elasticity and low-temperature performance of the material. Polybutylene adipate-1,4-diol is used as the main component of the soft segment. Since the ester group in polybutylene adipate-1,4-diol has a large polarity, good crystallinity, and high cohesive strength, the water-based polyurethane has good cohesive strength and peel strength.
[0028] Isophorone diisocyanate and hexamethylene diisocyanate are used as the main components of the hard segment. Compared with aromatic polyisocyanates, the use of the above two aliphatic polyisocyanates as the hard segment makes the reaction conditions milder, and has certain yellowing resistance, which is convenient for storage, so that the polyurethane molecules can have better strength and hardness.
[0029] Dihydroxymethylacetic acid and sodium ethylenediamine sulfonate are added as carboxylate type hydrophilic chain extender and sulfonate type hydrophilic chain extender respectively, so that hydrophilic groups are introduced into the polyurethane molecules, thereby making the polyurethane molecules have a certain hydrophilicity.
[0030] At the same time, 1,4-butanediol is used. 1,4-butanediol can react with the isocyanate of isophorone diisocyanate and hexamethylene diisocyanate to generate carbamate groups. The generated carbamate groups can further form hydrogen bonds with poly(1,4-butanediol adipate), thereby further improving the strength and hardness of the polyurethane molecules.
[0031] Preferably, the coating film is prepared from raw materials comprising the following weight percentages:
[0032]
[0033] By adopting the above technical solution, brown algae polysaccharide is added as the main polysaccharide, which is easily soluble in water and has good viscosity. Brown algae polysaccharide is used as the main film-forming coating film; glycerol and gelatin are added as the main film-forming auxiliary materials. Gelatin has good hydrophilicity and can form a colloid, which is helpful for the subsequent film-forming work of the coating film. Glycerol is also added as a polyol, which can play a plasticizing role on the coating film. At the same time, when the coating film is subjected to a certain temperature, it will further soften and degrade. Therefore, during the initial positioning of the touch switch, the coating film will be spontaneously softened and degraded by the heat generated by the initiator and the heat-generating agent, and the connecting channel will be blocked and separated from the outer bubble film.
[0034] Preferably, the coating film is prepared by the following process steps:
[0035] Add brown algae polysaccharide, glycerol and gelatin to distilled water in proportion to obtain solution A, heat and stir solution A, control the heating temperature to 80-90°C, control the stirring speed to 80-100r / min, control the heating and stirring time to 20-30min, and obtain a coating film liquid, cool the coating film liquid to room temperature, perform ultrasonic oscillation on the coating film liquid, and dry the coating film liquid after ultrasonic oscillation to obtain the coating film.
[0036] By adopting the above technical scheme, brown algae polysaccharide, glycerol and gelatin are configured into a solution, and the dissolution rate of each component in distilled water is accelerated by heating and stirring. At the same time, the property of gelatin to form a colloid after heating is utilized to prepare a coating film liquid; finally, the coating film liquid is oscillated by an ultrasonic cleaning machine to obtain a coating film liquid in which each component is evenly distributed and relatively stable, so as to carry out drying and film forming.
[0037] In summary, this application has the following beneficial effects:
[0038] 1. The touch circuit in the present application adds a transparent insulating layer and conductive oil. Compared with the original contact and connection method between the upper contact of the control circuit and the lower plate of the control circuit, it avoids the situation where the contact and the plate are in insufficient contact after multiple contacts as much as possible. The capacitive touch effect is achieved by using the conductive oil, and the change of capacitance is used to control the touch circuit, which can improve the service life of the touch switch to a certain extent.
[0039] 2. In the present application, the setting of hot melt adhesive, heating agent and initiator is preferably adopted. Compared with the traditional combination of release paper and adhesive layer, the user only needs to align the touch switch with the installation position, and then use the heating effect generated by the initiator and heating agent to soften the hot melt adhesive and make it sticky, so as to achieve the initial installation and positioning of the touch switch on the surface of the device, thereby making the touch switch have better installation accuracy.
[0040] 3. In the present application, the coating film is combined with the initiator and the heating agent to make the adhesive layer of the touch switch non-sticky during storage, and the heating effect of the initiator and the heating agent is used to make the adhesive layer sticky when the touch switch is installed. At the same time, the coating film has the characteristic of decomposing by heating, so that the coating film does not affect the aesthetics of the touch switch after installation. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram of the exploded structure of the touch switch in this application;
[0042] Figure 2 yes Figure 1 A schematic diagram of the cross-sectional structure of the middle adhesive layer;
[0043] Figure 3 yes Figure 2 Schematic diagram of the cross-sectional structure at the middle connecting channel.
[0044] Explanation of the reference numerals: 100, pattern layer; 110, substrate; 120, touch switch circuit; 130, conductive oil; 140, carbon paste; 150, silver paste circuit; 160, transparent insulating layer; 180, adhesive layer; 190, microgroove; 200, inner bubble film; 210, outer bubble film; 220, connecting channel; 230, connecting film; 240, fixing ring; 250, connecting bridge; 260, fixing tube; 270, piston; 280, through hole; 290, touch circuit. DETAILED DESCRIPTION
[0045] The present application is further described in detail below in conjunction with the accompanying drawings, embodiments, preparation examples and comparative examples.
[0046] Preparation Example
[0047] Preparation Example 1
[0048] A hot melt adhesive is prepared from the following raw materials in parts by weight: 300g of poly(1,4-butylene adipate); 30g of dimethylol propionic acid; 30g of sodium ethylenediamine sulfonate; 100g of isophorone diisocyanate; 50g of hexamethylene diisocyanate; 20g of 1,4-butylene glycol; 50g of acetone; and 50g of triethylamine.
[0049] Among them, poly(1,4-butylene adipate) was selected from poly(1,4-butylene adipate) with a molecular weight of 2000 produced by West Asia Chemical Technology Co., Ltd.; dimethylol propionic acid, isophorone diisocyanate, hexamethylene diisocyanate, and 1,4-butanediol were all selected from Shanghai Jinjinle Industrial Co., Ltd.; sodium ethylenediamine sulfonate was selected from Hubei Hongxin Ruiyu Fine Chemical Co., Ltd.;
[0050] A preparation process of hot melt adhesive specifically includes the following process steps:
[0051] Step 1, adding 300 g of poly(1,4-butylene adipate) with a molecular weight of 2000 into a three-necked flask in proportion, and performing vacuum distillation on the poly(1,4-butylene adipate) with a molecular weight of 2000, controlling the vacuum distillation temperature to 120° C. and the vacuum distillation time to 1 hour;
[0052] Step 2, after the vacuum distillation is completed, the three-necked flask is maintained at normal pressure, the temperature in the three-necked flask is controlled to 70°C, 100g of isophorone diisocyanate, 50g of hexamethylene diisocyanate and 20g of 1,4-butanediol are added to the three-necked flask in proportion, the temperature in the three-necked flask is maintained at 70°C, and after the reaction time is 15min, the temperature in the three-necked flask is raised to 85°C, and the reaction time is controlled to 3h; after reacting for 3h, 30g of dimethylol propionic acid is added to the three-necked flask in proportion, and the reaction time is controlled to 2h;
[0053] Step 3, cooling the temperature in the three-necked flask to 40° C., then adding 50 g of acetone to the three-necked flask in proportion, then adding 50 g of triethylamine, controlling the reaction time to 30 min, and then adding 30 g of sodium ethylenediaminesulfonate to the three-necked flask, controlling the reaction time to 1 h, to obtain a crude product hot melt adhesive;
[0054] Step 4, adding deionized water to the crude hot melt adhesive for emulsification and dispersion, distilling under reduced pressure, controlling the temperature to 60° C., and controlling the reaction time to 15 min to obtain the hot melt adhesive.
[0055] Preparation Example 2-5
[0056] The differences between the raw material ratio parameters and process parameters in Preparation Examples 2-5 and Preparation Example 1 are recorded in Table 1, and the rest are the same as Preparation Example 1.
[0057] Table 1 Ratio parameters and process parameters of raw materials in preparation examples 2-5 hot melt adhesive
[0058]
[0059]
[0060] Preparation Example 6
[0061] A heating agent is prepared from the following raw materials in parts by weight: 12g Al powder; 10g activated carbon;
[0062] A preparation process of a heat-generating agent specifically includes the following process steps:
[0063] Take Al2O3 raw material, mechanically crush the Al2O3 raw material, and sieve it with a 400-mesh sieve to obtain Al2O3 powder, then use hydrogen to perform hydrogenation reduction reaction on the Al2O3 powder to obtain Al powder with a rough surface and sponge-like pores inside, pass inert gas nitrogen into the Al powder, and then add activated carbon particles with a particle size of 200 μm into the Al powder while keeping the inert gas nitrogen passing, fill the Al powder into the pores of the activated carbon particles to obtain a heat-generating agent.
[0064] Preparation Example 7-10
[0065] The differences between the ratio parameters of the raw materials in Preparation Examples 7-10 and Preparation Example 6 are recorded in Table 2, and the rest are the same as Preparation Example 6.
[0066] Table 2 Ratio parameters of raw materials in the exothermic agent of Preparation Examples 7-10
[0067]
[0068] Preparation Example 11
[0069] An initiator is prepared from the following raw materials in parts by weight: 12g of sodium bicarbonate solid; 4g of calcium oxide; wherein the calcium oxide has a particle size of 500μm.
[0070] Preparation Examples 12-15
[0071] The differences between the ratio parameters of the raw materials in Preparation Examples 12-15 and Preparation Example 11 are recorded in Table 3, and the rest are the same as Preparation Example 11.
[0072]
[0073] Preparation Example 16
[0074] A coating film is made of the following raw materials in parts by weight: 14g of brown algae polysaccharide; 20g of glycerol; 14g of gelatin; 152g of distilled water;
[0075] A preparation process of a coating film specifically includes the following process steps:
[0076] S1, taking raw material Sargassum fusiformis, washing the Sargassum fusiformis, drying the washed Sargassum fusiformis, crushing the dried Sargassum fusiformis to obtain Sargassum fusiformis powder, adding the Sargassum fusiformis powder to distilled water for heating and leaching, repeating the heating and leaching for 3 times, controlling the heating temperature to be 90° C., obtaining an extract, centrifuging the extract, taking the supernatant of the centrifuged extract, heating and concentrating the supernatant to obtain a concentrated solution with a high concentration, adding anhydrous ethanol to the concentrated solution, centrifuging the concentrated solution after the addition of anhydrous ethanol to obtain a precipitate, filtering and drying the precipitate to obtain brown algae polysaccharide;
[0077] S2. 14 g of brown algae polysaccharide, 20 g of glycerol and 14 g of gelatin are added to 152 g of distilled water in proportion to obtain solution A, and solution A is heated and stirred. The heating temperature is controlled to be 80°C, the stirring speed is controlled to be 80 r / min, and the heating temperature and stirring time are controlled to be 20 min to obtain a coating film liquid. The coating film liquid is cooled to room temperature, and then the coating film liquid is oscillated by an ultrasonic cleaning machine, and the coating film liquid after oscillation by the ultrasonic cleaning machine is dried to obtain a coating film.
[0078] Preparation Examples 17-20
[0079] The differences between the raw material ratio parameters and process parameters in Preparation Examples 17-20 and Preparation Example 11 are recorded in Table 3, and the rest are the same as Preparation Example 16.
[0080] Table 3 Ratio parameters and process parameters of raw materials in preparation examples 17-20
[0081]
[0082] Example
[0083] Example 1
[0084] Reference Figure 1 A touch switch with a 3D effect includes a pattern layer 100, a substrate 110 and a touch switch circuit 120 arranged in sequence; it also includes an adhesive layer 180, which can be located on the side of the pattern layer 100 away from the substrate 110, or on the side of the transparent insulating layer 160 away from the substrate 110. The pasting position of the adhesive layer 180 can be adjusted according to the final pasting requirements.
[0085] The pattern layer 100 is preferably printed by a UV color ink printer. The 3D digital pattern is directly input into the printer. The printer sprays UV color ink and UV cures while printing. The pattern layer 100 is translucent. The pattern layer 100 can also be printed by lithography, letterpress printing, gravure printing and screen printing. The touch switch circuit 120 is sequentially provided with conductive oil 130, carbon paste 140, silver paste circuit 150 and transparent insulating layer 160 along the direction from the pattern layer 100 to the substrate 110. The conductive oil 130 is transparent and composed of PEDOT.
[0086] The adhesive layer 180 is made of polyacrylate pressure-sensitive adhesive produced by Shangyu Lai Tejia Chemical Co., Ltd. and is matched with release paper.
[0087] Example 2
[0088] The difference between Example 2 and Example 1 is: Figure 2 The adhesive layer 180 is made of 8g hot melt adhesive, and the hot melt adhesive is provided with a plurality of microgrooves 190 spaced apart along the circumference direction. The hot melt adhesive is provided with a plurality of connecting channels 220, and each connecting channel 220 corresponds to each microgroove 190 one by one, and each connecting channel 220 is connected to the corresponding microgroove 190, and one end of the connecting channel 220 away from the microgroove 190 is connected to the outside, and 0.6g of heating agent and 0.6g of initiator are placed in the microgroove 190.
[0089] The hot melt adhesive selected is the hot melt adhesive DFHM-B produced by Jingjiang Dongfang Chemical Co., Ltd., the heating agent selected is calcium oxide, and the initiator selected is water, wherein the water is sprayed into the micro groove 190.
[0090] Example 3
[0091] The difference between Example 3 and Example 2 is that: 0.8g of coating film is also placed in the adhesive layer 180, the coating film is selected from the coating film prepared in Preparation Example 16, the coating film is placed in the microgroove 190, the initiator is placed in the coating film, and the heating agent is placed in the microgroove 190 and outside the coating film.
[0092] Example 4
[0093] The difference between Example 4 and Example 3 is that the hot melt adhesive is the hot melt adhesive prepared in Preparation Example 1.
[0094] Example 5
[0095] The difference between Example 5 and Example 3 is that the exothermic agent is the exothermic agent prepared in Preparation Example 6.
[0096] Example 6
[0097] The difference between Example 6 and Example 3 is that the exothermic agent is the exothermic agent prepared in Preparation Example 6, and the initiator is the initiator prepared in Preparation Example 11.
[0098] Example 7
[0099] The difference between Example 7 and Example 3 is that the hot melt adhesive is the hot melt adhesive prepared in Preparation Example 1, the exothermic agent is the exothermic agent prepared in Preparation Example 6, and the initiator is the initiator prepared in Preparation Example 11.
[0100] Example 8
[0101] The difference between Example 8 and Example 7 is: Figure 2 and Figure 3 The coating film is prepared into a sealed inner bubble film 200 and an outer bubble film 210, the inner bubble film 200 is placed in the microgroove 190 of the adhesive layer 180 and is filled with nitrogen, the initiator is located in the inner bubble film 200, the initial volume of the inner bubble film 200 is smaller than the microgroove 190, the heating agent is located in the microgroove 190 and is located outside the inner bubble film 200. The outer bubble film 210 is located outside the adhesive layer 180 and is filled with oxygen, a connecting bridge 250 is provided between the inner bubble film 200 and the outer bubble film 210, the connecting bridge 250 is located in the connecting channel 220, and the outer peripheral wall of the connecting bridge 250 is tightly pressed against the peripheral side wall of the connecting channel 220.
[0102] A fixing ring 240 is fixedly arranged inside the connecting bridge 250, the outer peripheral wall of the fixing ring 240 is fixedly connected to the inner peripheral wall of the connecting bridge 250, a fixing tube 260 is fixedly connected to the inner peripheral wall of the fixing ring 240, a piston 270 is slidably connected inside the fixing tube 260, through holes 280 are opened on both ends of the peripheral side walls of the fixing tube 260 along the axial direction of the fixing tube 260, and the piston 270 is located between the two through holes 280, the roughness of the inner peripheral wall of the end of the fixing tube 260 close to the inner bubble film 200 is greater than the roughness of the inner peripheral wall of the end of the fixing tube 260 away from the inner bubble film 200, and the air pressure inside the outer bubble film 210 is equal to the air pressure inside the inner bubble film 200. A connecting film 230 is connected between each outer bubble film 210 located outside the adhesive layer 180, and the connecting film 230 plays the role of buffering and protecting the outer bubble film 210.
[0103] Examples 9-12
[0104] The differences between the composition ratios of the adhesive layers in Examples 9-12 and Example 8 are shown in Table 5.
[0105] Table 5: Ratio of components included in the adhesive layer in Examples 9-12
[0106]
[0107] Examples 13-16
[0108] The differences between the composition ratios of the adhesive layers in Examples 13-16 and Example 8 are shown in Table 6.
[0109] Table 6 Ratio of components included in the adhesive layer in Examples 13-16
[0110]
[0111]
[0112] Comparative Example
[0113] Comparative Example 1
[0114] The difference between Comparative Example 1 and Example 1 is that the touch switch consists of a panel layer, a surface adhesive layer, an upper control circuit layer, a lower control circuit layer, an interlayer layer and a back adhesive layer, and the back adhesive is made of polyacrylate pressure-sensitive adhesive produced by Shangyu LaiTjia Chemical Co., Ltd. and is matched with release paper.
[0115] Comparative Example 2
[0116] The difference between Comparative Example 2 and Example 2 is that no hot melt adhesive is added.
[0117] Comparative Example 3
[0118] The difference between Comparative Example 3 and Example 2 is that no exothermic agent is added.
[0119] Comparative Example 4
[0120] The difference between Comparative Example 4 and Example 2 is that no initiator is added.
[0121] Comparative Example 5
[0122] The difference between Comparative Example 5 and Example 2 is that no initiator and exothermic agent are added.
[0123] Performance testing
[0124] For the embodiments 1-16 and comparative examples 1-4 of the present application, the performance test of the touch switch was performed, and the service life of the touch switch was tested, and the number of key presses required when the touch switch was not sensitive was detected, and the service life was distinguished by ten thousand times, accurate to 2 decimal places;
[0125] The installation accuracy and aesthetics of the touch switches of each component were observed after installation. The evaluation standard for installation accuracy was the deviation between the actual installation position of the touch switch and the predetermined installation position. The evaluation standard for aesthetics was the completeness of the touch switch after installation and whether the touch switch needed to be wiped and cleaned a second time. The installation accuracy and aesthetics were differentiated on a scale of 1-10, with 1 being the lowest installation accuracy and aesthetics, and 10 being the highest installation accuracy and aesthetics, and 1-10 being counted with 0.1 as the order of magnitude.
[0126] Each set of touch switches was pasted on the steel plate surface after removing oil and oxide. The touch switches with pressure-sensitive adhesive were pasted by peeling off the release paper and pressing back and forth. The touch switches with initiator, heating agent and hot melt adhesive were pre-positioned by using the initiator and heating agent, and then the center of the touch switch was heated by the heat source. The 180° peel strength test was carried out according to GB / T 2792-1998. The test results are shown in Table 7.
[0127] Table 7 Performance test data table
[0128]
[0129]
[0130] It can be seen from Examples 1-16 and Comparative Examples 1-5 and Table 7 that the touch circuit of the touch switch is composed of conductive oil, carbon paste, silver paste circuit and transparent insulating layer, which can significantly improve the service life of the touch switch compared to the touch circuit of the touch switch being controlled by touch between the upper layer of the control circuit and the lower layer of the control circuit.
[0131] Combining Examples 1-8 and Comparative Examples 1-5 with Table 7, it can be seen that the touch switch uses a combination of hot melt adhesive, heating agent, and initiator, which can improve the installation accuracy of the touch switch after it is installed on the surface of the device compared to the combination of traditional pressure-sensitive adhesive and release paper. At the same time, the heating agent, initiator, and coating film in this application can further improve the installation accuracy of the touch switch after it is installed on the surface of the device. The use of structures such as the inner and outer bubble films of the coating film in this application can significantly improve the installation accuracy of the touch switch.
[0132] It can be seen from Examples 1-8 and Comparative Examples 1-5 and Table 7 that the touch switch uses a combination of hot melt adhesive, heating agent and initiator, which can improve the aesthetics of the touch switch after it is installed on the surface of the device compared to the combination of traditional pressure-sensitive adhesive and release paper. The use of the heating agent, initiator and coating film in the present application can further improve the aesthetics of the touch switch after installation. At the same time, the use of structures such as the inner and outer bubble films of the coating film in the present application can significantly improve the aesthetics of the touch switch.
[0133] From Examples 1-16 and Comparative Examples 1-5 and Table 7, it can be seen that the touch switch using the hot melt adhesive in the present application has better peel strength than that using an ordinary hot melt machine; the use of a coating film can further preserve the effectiveness of the heating agent, and can improve the peel strength at the edge of the touch switch, thereby improving the overall peel strength of the touch switch; the use of structures such as the inner and outer bubble films of the coating film in the present application can better protect the heating agent, greatly reduce the amount of failure of the heating agent, thereby ensuring the peel strength at the edge of the touch switch, thereby improving the overall peel strength of the touch switch.
[0134] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A touch switch with 3D effect, characterized in that: The invention comprises a pattern layer (100), a substrate (110) and a touch switch circuit (120) which are arranged in sequence, wherein the touch switch circuit (120) is provided with conductive oil (130), carbon paste (140), a silver paste circuit (150) and a transparent insulating layer (160) in sequence along the direction from the pattern layer (100) to the substrate (110), and the pattern layer (100) or the transparent insulating layer (160) is provided with an adhesive layer (180); wherein the adhesive layer (180) is composed of hot melt adhesive, and the adhesive layer (180) is provided with a plurality of microgrooves (190) at intervals, and connection channels (220) respectively connected to each of the microgrooves (190), the connection channels (220) being connected to the outside, and an initiator and a heat generating agent being provided in the microgrooves (190).
2. A touch switch with 3D effect according to claim 1, characterized in that: The adhesive layer (180) is also provided with a coating film, the coating film is placed in the microgroove (190), the initiator is placed in the coating film, and the heat-generating agent is located outside the coating film.
3. A touch switch with 3D effect according to claim 2, characterized in that: The coating film is prepared into a sealed inner bubble film (200) and an outer bubble film (210), the inner bubble film (200) is placed in the microgroove (190) and filled with nitrogen, the initiator is located in the inner bubble film (200), the outer bubble film (210) is located outside the adhesive layer (180) and filled with oxygen, the pressure inside the outer bubble film (210) and the inner bubble film (200) are equal, a connecting bridge (250) is provided between the inner bubble film (200) and the outer bubble film (210), a fixing ring (240) is provided in the connecting bridge (250), the outer peripheral wall of the fixing ring (240) is connected to the inner wall of the connecting bridge (250), a fixing tube (260) is connected to the inner peripheral wall of the fixing ring (240), a piston (270) is slidably connected in the fixing tube (260), and the fixing tube (260) Through holes (280) are provided on the side walls at both ends, and the piston (270) is located between the two through holes (280).
4. A touch switch with 3D effect according to any one of claims 1 to 3, characterized in that: The initiator is composed of Al powder and activated carbon in a mass ratio of (6-8): (5-7).
5. A touch switch with 3D effect according to any one of claims 1 to 3, characterized in that: The exothermic agent is composed of sodium bicarbonate and calcium oxide in a mass ratio of (6-8): (2-3).
6. A touch switch with 3D effect according to any one of claims 1-3, characterized in that: The hot melt adhesive is made of the following raw materials in parts by weight: 30-40 parts of poly(1,4-butylene adipate); 3-5 parts of dimethylolpropionic acid; 3-5 parts of sodium ethylenediaminesulfonate; Isophorone diisocyanate 10-20 parts; Hexamethylene diisocyanate 5-10 parts; 1,4-Butanediol 2-3 parts.
7. A touch switch with 3D effect according to claim 6, characterized in that: The mass ratio of the dimethylolpropionic acid to sodium ethylenediaminoethanesulfonate is 1:1, and the mass ratio of the isophorone diisocyanate to hexamethylene diisocyanate is 2:
1.
8. A touch switch with 3D effect according to claim 2 or 3, characterized in that: The coating film is prepared from raw materials comprising the following weight percentages: Fucoidan 7-13%; Glycerol 10-17%; Gelatin 7-13%; Distilled water balance.
9. A touch switch with 3D effect according to claim 8, characterized in that: The coating film is prepared by the following process steps: adding brown algae polysaccharide, glycerol and gelatin to distilled water in proportion to obtain solution A, heating and stirring solution A, controlling the heating temperature to 80-90°C, controlling the stirring speed to 80-100r / min, and controlling the heating and stirring time to 20-30min to obtain a coating film liquid, cooling the coating film liquid to room temperature, ultrasonically oscillating the coating film liquid, and drying the coating film liquid after ultrasonic oscillation to obtain the coating film.
Citation Information
Patent Citations
Membrane switch
CN204130405U
Take touch switch's control panel
CN205507720U
Film formula touch switch of microwave oven usage
CN205961084U